Hayabusa2 asteroid sample return mission : technological innovation and advances - Hirabayashi, Masatoshi; Tsuda, Yuichi (Elsevier, 2022)
Hayabusa2 Asteroid Sample Return Mission: Technological Innovation and Advances covers the second Japanese asteroid sample return mission. The purpose of the mission is to survey the asteroid Ryugu's surface features, touch down on the asteroid, form an artificial crater by shooting an impactor, and collect sample materials. This book covers these operations, along with everything known about key technologies, hardware and ground systems upon Hayabusa2's return to Earth in 2020. This book is the definitive reference on the mission and provides space and planetary scientists with information on established technologies to further advance the knowledge and technologies in future space exploration missions.